2016
DOI: 10.1016/j.psychsport.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring athletes' perceptions of the relationship between mental toughness and dispositional flow in sport

Abstract: Objectives\ud \ud Despite considerable scholarly attention over the last two decades, little is known about the influence of dispositional attributes on flow in sport. In achievement settings, mental toughness (MT) is a personal capacity supporting the process of high performance. Based on common overlaps with peak performance, confidence, control, concentration, and thriving in demanding situations, the present research aimed to explore the relationship between MT and dispositional flow and elucidate the psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…Specifically, MT has often been associated with setting exceedingly challenging performance expectations and maintaining commitment towards reaching such standards. 28,30 These descriptions represent efforts mentally tough athletes direct towards achieving subjective markers of performance and outperforming competitors, which align closely with characterisations of perfectionistic strivings. There is also a self-to-other comparative component to PSP, as athletes who strive for perfection tend to believe they have higher performance standards and achievement goals than their competitors.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Specifically, MT has often been associated with setting exceedingly challenging performance expectations and maintaining commitment towards reaching such standards. 28,30 These descriptions represent efforts mentally tough athletes direct towards achieving subjective markers of performance and outperforming competitors, which align closely with characterisations of perfectionistic strivings. There is also a self-to-other comparative component to PSP, as athletes who strive for perfection tend to believe they have higher performance standards and achievement goals than their competitors.…”
Section: Discussionmentioning
confidence: 87%
“…coaches) have described MT as consistently striving to achieve one's best, setting and expecting high standards to be met, being committed to performance excellence and attaining success and pushing physical and mental limits to set oneself apart from competitors. [28][29][30] Furthermore, both athletes 31 and coaches 32 have suggested that athletes' MT development is predicated on high self-and other-initiated expectations (e.g. coach) and encouraging athletes' pursuit of such ideals.…”
Section: Perfectionism Mental Toughness and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, while some consistencies lie across the various conceptualisations of MT (e.g. it features attributes such as confidence, perseverance, and emotional control; Jackman, Swann, & Crust, ), the present image is that of a multi‐pronged concept, underlined by a range of competing assumptions.…”
Section: Mental Toughnessmentioning
confidence: 89%
“…elite athletes, runners, hockey players, soccer players, coaches, soccer referees), there are also specific attributes to each sport and the respective roles played [7,11,12,13,14]. For example, Slack et al, (2012) have studied referees to understand mental toughness in soccer officiating.…”
Section: Introductionmentioning
confidence: 99%